La defensa del Consejo Comunitario de la cuenca del Río Yurumangui: Memoria y territorio - Arango Vallejo, Juanita (Notas de Antropología de las Américas, 2025)
In the Yurumangui River lives an Afro-descendant community that arrived on the Colombian Pacific coast under conditions of slavery during the colonial period. Since then, they have been developing and living a reality shaped by their history and context, which has been deeply affected by the Colombian armed conflict for decades. This article examines the role of memory as a tool for defending the territory against the threats faced by the community of Yurumanguí.